Application of Digital Image Correlation to composite reinforcements testing. (15th January 2017) - Tekieli, Marcin; De Santis, Stefano; de Felice, Gianmarco; Kwiecień, Arkadiusz; Roscini, Francesca
Abstract: Digital Image Correlation (DIC) is a full-field contactless optical method for measuring displacements in experimental testing, based on the correlation of the digital images taken during test execution. It is used in several fields of experimental solid mechanics, but its potential application to the characterization of composite reinforcements has not been fully investigated yet. In this paper DIC is used in tensile and bond tests on composite reinforcements comprising different textiles and matrices. Results obtained by two DIC software programs are validated by comparison with displacement and strain transducers. DIC provides additional information on damage pattern (crack location and width) and composite-to-substrate load transfer mechanism (effective bond length and local stress concentrations). It also offers the advantageous possibility of selecting several measurement points after the test, overcoming some drawbacks of traditional transducers. On the other hand, since only on the outer surface of the specimen is monitored, no information is directly available on the textile embedded in the matrix. The combination of DIC and traditional sensors in laboratory testing allows improving the understanding of the mechanical behaviour of composite reinforcements and the identification of their fundamental properties.